Obstacle Negotiation in Older Adults: Prefrontal Activation Interpreted Through Conceptual Models of Brain Aging. Issue 4 (10th August 2020) - Chatterjee, Sudeshna A; Seidler, Rachael D; Skinner, Jared W; Lysne, Paige E; Sumonthee, Chanoan; Wu, Samuel S; Cohen, Ronald A; Rose, Dorian K; Woods, Adam J; Clark, David J
Abstract: Background and Objectives: The influence of interindividual differences on brain activation during obstacle negotiation and the implications for walking performance are poorly understood in older adults. This study investigated the extent to which prefrontal recruitment during obstacle negotiation is explained by differences in age, executive function, and sex. These data were interpreted according to the Compensation-Related Utilization of Neural Circuits Hypothesis (CRUNCH) framework of brain aging. We also tested the association between prefrontal recruitment and walking performance. Research Design and Methods: Prefrontal oxygenated hemoglobin concentration (O2 Hb) was measured during typical walking ( Typical ) and obstacle negotiation ( Obstacles ) tasks in 50 adults aged 65 years and older using functional near-infrared spectroscopy. The primary outcome was the change in prefrontal recruitment (∆PFR), measured as Obstacles ∆O2 Hb minus Typical ∆O2 Hb. Multiple regression was used to test the relationship between ∆PFR and age, executive function measured by the Trail Making Test, and sex. Pearson's correlation coefficient was used to investigate the association between ∆PFR and the cost of Obstacles walking speed relative to Typical walking. Results: Age, executive function, and their interaction significantly predicted greater ∆PFR ( R 2 = 0.34, p = .01). Participants were subgrouped according to age and executive function to examine the interaction effects. Adults of lower age and with lower executive function exhibited greater ∆PFR during Obstacles compared to their peers with higher executive function ( p = .03). Adults of advanced age exhibited a ceiling of prefrontal recruitment during obstacle negotiation, regardless of executive function level ( p = .87). Greater ∆PFR was significantly associated with a smaller cost of Obstacles ( r = 0.3, p = .03). Discussion and Implications: These findings are consistent with the CRUNCH framework: neural inefficiency where a greater amount of brain activation is needed for task performance at a similar level, compensatory overactivation to prevent a steeper decline in task performance, and capacity limitation with a recruitment ceiling effect.